2013
DOI: 10.1371/journal.pone.0056508
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Macrophages and Nitric Oxide in Interleukin-3-Enhanced HSV-Sr39tk-Mediated Prodrug Therapy

Abstract: The herpes simplex virus thymidine kinase/ganciclovir (HSV-sr39tk/GCV) system is a well-established prodrug system used in cancer gene therapy. However, this system is currently not effective enough to eradicate malignant tumors completely. This study aimed to evaluate whether co-expression of interleukin-3 (IL-3) could enhance the anti-tumor activity of HSV-sr39tk/GCV prodrug gene therapy using a murine TRAMP-C1 prostate tumor model. In vitro results demonstrated that HSV-sr39tk-transfected cells exhibited en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…IL-3 can also activate macrophages to increase the expression of MHC class II molecules and IL-1 37 . The use of IL-3 has also been reported to enhance macrophage-dependent anti-tumor effects when utilized in combination with cancer gene therapy 38 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-3 can also activate macrophages to increase the expression of MHC class II molecules and IL-1 37 . The use of IL-3 has also been reported to enhance macrophage-dependent anti-tumor effects when utilized in combination with cancer gene therapy 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Other accessory factors such as NO are involved in the progression of infected cells to full neoplastic phenotype. NO can inhibit the replication of a variety of viruses, such as murine poxvirus and herpes viruses including HSV and Epstein-Barr virus (EBV), and RNA viruses including coxsackievirus (Yu et al, 2013;Gao, et al, 1999;Akaike and Maeda, 2000). In this study we found that in SiHa cells with integrated HPV, NO caused dose and time dependent inhibition of the expression of HPV early gene E6 mRNA, indicating that NO inhibits the replication of HPV.…”
Section: Discussionmentioning
confidence: 56%
“…The HSV-sr39tk suicide gene constructed by Dr. Ching-Fang Yu [37] was transfected into ALTS1C1 by Effectene Transfection Reagent (QIAGEN, 1054250, Mainz, Germany). Briefly, 1 µg of plasmid DNA diluted to a total of 150 µL and mixed with 8 µL Enhancer and kept at room temperature for 4 min.…”
Section: Plasmids and Cell Transfectionmentioning
confidence: 99%
“…Even local radiation therapy (RT) in this model stimulates myelopoiesis and modifies the tumor microenvironment in favor of anti-inflammatory M2 TAMs, which promote tumor recurrence [39]. Interestingly, in another model of tk/GCV gene therapy combined with IL-3 immune therapy in a prostate tumor model, M1 macrophages were generated that had anti-tumor efficacy with NO production [37]. Our aim here was to specify the roles of CD11b + Gr-1 − myeloid cells in ALTS1C1 tumors following chemotherapy.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation